The Stability Conditions of the Pump Structure Vibration - Al Hariri, Nassir Hassan Abdul Hussain (Al-Khwarizmi Engineering Journal, 2012)
The general approach of this research is to assume that the small nonlinearity can be separated from the linear part of the equation of motion. The effect of the dynamic fluid force on the pump structure system is considered vibrates at its natural frequency but the amplitude is determined by the initial conditions. If the motion of the system tends to increase the energy of the pump structure system, the vibration amplitude will increase and the pump structure system is considered to be unstable. A suitable MATLAB program was used to predict the stability conditions of the pump structure vibration. The present research focuses on fluid pump problems, namely, the role played by damping coefficient C, damping factor D and angular speed ω (termed the ratio () and the determining stability of a centrifugal pump structure. The data demonstrate substantial rotor dynamic effects, a destabilizing chart appears to be inversely proportional to the D, C, and ω, and resonance changes significantly with flow rate.